2021
DOI: 10.1002/ccd.29807
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, predictors and clinical impact of permanent pacemaker insertion in women following transcatheter aortic valve implantation: Insights from a prospective multinational registry

Abstract: Objectives: To describe the incidence, predictors, and clinical impact of permanent pacemaker insertion (PPI) following transcatheter aortic valve replacement (TAVR) in women.Background: Data on pacemaker insertion complicating TAVR in women are scarce.Methods: The Women's International Transcatheter Aortic Valve implantation (WIN-TAVI) is a prospective registry evaluating the safety and efficacy of TAVR in women.We included patients without preprocedural pacemakers and divided them into two groups: (1) PPI an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…Ferreira T et al ( 25 ) demonstrated that increased H-V interval, which showed in post-TAVR electrophysiological study, was the best predictor of PPM implantation undergoing TAVR. A previous study by Johny Nicolas et al ( 26 ) showed that RBBB before TAVR was the only predictor.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Ferreira T et al ( 25 ) demonstrated that increased H-V interval, which showed in post-TAVR electrophysiological study, was the best predictor of PPM implantation undergoing TAVR. A previous study by Johny Nicolas et al ( 26 ) showed that RBBB before TAVR was the only predictor.…”
Section: Discussionmentioning
confidence: 94%
“…All studies were cohort studies. RBBB prior to TAVR was considered to be a predictor in most of the selected studies ( 9 , 12 , 22 , 24 , 26 ) in Table 4 . However, the association of new-onset LBBB with PPM implantation after TAVR has not been fully characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EVO-LUTE LOW-RISK and PARTNER-3 studies have shown that TAVI is not inferior to SAVR, even in low-risk patients [71][72][73]. However, TAVI is associated with risks such as death, bleeding complications, atrioventricular blocks requiring a pacemaker, and stroke [74][75][76].…”
Section: Diagnosis and Treatment Of Aortic Stenosismentioning
confidence: 99%